2020
DOI: 10.13106/jafeb.2020.vol7.no8.333
|View full text |Cite
|
Sign up to set email alerts
|

Customer Satisfaction with Less than Container Load Cargo Services in HoChiMinh City, Vietnam

Abstract: This research has four specific objectives: (1) identifying factors that affect customer satisfaction with less than container load (LCL) cargo services of logistics companies in HoChiMinh City (HCMC), (2) measuring the level of impact of the factors, (3) testing the difference in satisfaction among groups of customers with different characteristics in terms of type of business and time of using LCL cargo services, and (4) proposing some management implications to improve the quality of LCL cargo services. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Surveys have shown that service recovery leads to customer loyalty (Khoa, 2020;Giao et al, 2020;Nguyen et al, 2020;Alam & Noor, 2020;Cheng et al, 2019). As previously mentioned, service recovery involves a service providers ac-tions to resolve problems caused by a failure (Sheth et al, 2000), and effective service recovery results in complainant satisfaction (Gandhi et al, 2019).…”
Section: Service Recovery Firm Responses Service Quality and Customer...mentioning
confidence: 98%
“…Surveys have shown that service recovery leads to customer loyalty (Khoa, 2020;Giao et al, 2020;Nguyen et al, 2020;Alam & Noor, 2020;Cheng et al, 2019). As previously mentioned, service recovery involves a service providers ac-tions to resolve problems caused by a failure (Sheth et al, 2000), and effective service recovery results in complainant satisfaction (Gandhi et al, 2019).…”
Section: Service Recovery Firm Responses Service Quality and Customer...mentioning
confidence: 98%
“…Based on the context of the study, the measures of customer retention will be based on customer satisfaction and loyalty. Customer Satisfaction: Satisfaction is the feeling of pleasure or disappointment of customers which occur from comparing performance expectations with actual performance, meaning that if the performance is below customer's expectations, such customer will be dissatisfied (Giao, Thy, Vuong, Tu, Vinh & Lien, 2020;To, Do, Bui & Pham, 2020;Schirmer, Ringle, Gudergan & Feistel,2018). Customer satisfaction is perceived as customers' evaluation of services after acquiring and utilsing them.…”
Section: Customer Retention Measuresmentioning
confidence: 99%
“…Satisfaction is a person's sensation of pleasure or disappointment that emerges from comparing product performance expectations with actual performance, implying that if the execution falls short of expectations, the consumer will be dissatisfied. (Giao et. al., 2020).…”
Section: Customer Satisfaction and Customer Loyaltymentioning
confidence: 99%